Barriers to establishment and growth of cottonwoods in Yellowstone National Park's northern range - Rose, Joshua Robert, author; Cooper, David J., advisor; Hobbs, N. Thompson, committee member; Hufbauer, Ruth A., committee member (Colorado State University. Libraries, 2012)
Riparian ecosystems play a vital role in water storage, sediment retention, nutrient and contaminant removal, and wildlife habitat in western North American landscapes. Cottonwood (Populus spp.) trees form the principle riparian forest type in the semi-arid western United States and therefore understanding their abundance and processes affecting establishment and survival are critical. Within Yellowstone National Park (YNP) herbivory by ungulates shapes ecosystem structure and function of riparian forests. However, our understanding of the interactions between herbivores and cottonwoods is largely from studies of domestic livestock grazing and may not reflect free ranging herds of wild ungulates. In this study I quantify the influence of stream hydrologic regime and herbivory on cottonwood establishment and growth along three rivers in Yellowstone's northern range. My research addresses three questions: 1) What is the current distribution and composition of cottonwood communities? 2) What is the relative influence of ungulates and hydrologic regime on cottonwood establishment? 3) Does herbivory by ungulates limit cottonwood height? Approximately 500,000 of the 1.9 million cottonwoods in Yellowstone established between 1996 and 1998, the years immediately following wolf (Canis lupus) reintroduction to YNP. Recruitment was driven by the largest sequence of peak stream flows in the 20 th century. The flows caused large scale channel changes, and provided suitable habitat for cottonwood seedling establishment and survival. The Lamar River cottonwood forest appears to regenerate following infrequent to rare large peak flow events as occur on many streams in western North America. However, Soda Butte Creek and the Gardner River cottonwoods exhibited nearly annual recruitment similar to other low-order montane streams. For the three rivers studied, over 92% of cottonwoods occur along the Lamar River. After the 1997 flood, establishment has been nearly continuous on the Lamar River with the resulting cottonwood biomass exceeding herbivore demand. However, even with their relatively low consumption rates bison are able to remove a significant proportion of total cottonwood production in the study areas and limit plant height and forage available to wintering elk. In the absence of human perturbation of bison populations, either in pre-history or today, bison and other ungulates shape their environment. Future investigation of how these species shape the structure of their environment will serve to inform management decisions and educate park visitors on habitat dynamics in a multi-herbivore system.
Keywords: bison; cottonwood; elk; herbivory; riparian; Yellowstone